Patient comfort level among various age groups during orthodontic treatment- a cross-sectional survey - PRIADARSINI T,; KUMAR, NAVEEN; GANAPATHY, DHANRAJ (The journal of contemporary issues in business and government, 2020)
Orthodontic patients experience pain and discomfort to a varying degree during the course of treatment. One of the most important goals of orthodontic dental care is helping patients in their attempts to reach an acceptable level of satisfaction with their oral cavity and dentition. Dentofacial problems have known definitive effects on patient satisfaction and comfort with their appliance because it affects esthetics, performance, and function. The aim of this study was to assess the comfort level among various age groups during the orthodontic treatment. A questionnaire comprising 13 questions was created in an online survey platform and the link was shared to the patients . The patient data was collected from the case records of patients visiting Saveetha dental College for treatment. Statistical analysis was done using IBM SPSS software version 20.0. 44% of the respondents feel that their appliance is not at all comfortable and about 32% of the people are embarrassed to wear the appliance in public. Chi-square test was done for the association of gender and embarrassment of wearing appliances in public and the p value 0.001* was found to be statistically significant . This concludes that more male patients feel embarrassed to wear the appliance in public and patients of age group 15-20 years feel that the appliance is more tight , eliciting pain.